1986
DOI: 10.1139/y86-178
|View full text |Cite
|
Sign up to set email alerts
|

Effects of subchronic pyridostigmine pretreatment on the toxicity of soman

Abstract: The effect of subchronic pyridostigmine pretreatment on the toxicity of soman, in the absence of supporting therapy (atropine, oxime, and (or) anticonvulsant), as well as its effect on muscarinic cholinoceptor binding characteristics was assessed in the rat. Pretreatment with pyridostigmine by means of an implanted Alzet osmotic minipump for a 5-day total exposure dose of 12 mg/kg inhibited whole blood acetylcholinesterase activity by 73%. This pyridostigmine pretreatment lowered the soman LD50 from 104 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…It has been shown that therapeutic concentrations of 2-PAM are quite high in rat plasma and serum (1.4-5.5 mg/ml; [27] up to 100 mg/ml; [26] 0.7-3.3 mg/ml [28] ), in sheep plasma (up to 7 mg/ ml, [33] and in human plasma and serum (0.5-3 mg/ml; [23,24] 3-6 mg/ml; [25] 3-15 mg/ml [12,13] ). Concentrations in human urine were more than 100-times higher (250-2000 mg/ml [20] ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that therapeutic concentrations of 2-PAM are quite high in rat plasma and serum (1.4-5.5 mg/ml; [27] up to 100 mg/ml; [26] 0.7-3.3 mg/ml [28] ), in sheep plasma (up to 7 mg/ ml, [33] and in human plasma and serum (0.5-3 mg/ml; [23,24] 3-6 mg/ml; [25] 3-15 mg/ml [12,13] ). Concentrations in human urine were more than 100-times higher (250-2000 mg/ml [20] ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the DAD was set to these values for quantitative measurement under standard conditions. However, earlier reports applied a broad variety of different wavelengths, for example, 262, 270, 280, 290, 294, and 300 nm [13,28,29,[34][35][36] to detect 2-PAM quantitatively. These values may be due to different HPLC solvent components, the pH used, or simply to non-optimum settings.…”
Section: Photometric Characterization Of 2-pam and 4-paomentioning
confidence: 99%
See 1 more Smart Citation
“…This study shows that PB above 40 mg/kg is toxic in concern to hematology, serum biochemical parameters and physiology of liver and kidney when administered for over one month continuously. It is important to realize that PB is not an antidote and it has no value when administered after nerve-agent exposure [44]. PB is an antidote enhancer rather than a pretreatment capable of acting by itself in the absence of antidotes [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that a 5-d exposure to PB did not alter muscarinic receptor binding in the brain or ileum of rat. 22 Additionally, the cholinesterase inhibitor soman has been shown to result in miotic tolerance without decreasing the number of muscarinic receptors on the pupillary sphincter muscle. 17 Thus, it is not likely that a decreased number of muscarinic receptors, secondary to internalization or decreased synthesis, is responsible for the observed tolerance.…”
Section: Figmentioning
confidence: 99%